2022-RA-1433-ESGO Reproductive outcomes after conservative treatment in malignant ovarian germ cell tumors (MOGCTs) patients: a MITO-9 study. (20th October 2022) - Bergamini, Alice; Vasta, Francesca; Bocciolone, Luca; Scarfone, Giovanna; Cassani, Chiara; Ferrandina, Gabriella; de Vivo, Rocco; Danese, Saverio; Filippo, Marianna Di; Grassi, Elisa; Cormio, Gennaro; Pignata, Sandro; et al.
Abstract : Introduction/Background: Malignant ovarian germ cell tumours (MOGCTs) are rare tumours mainly affecting women in reproductive age, hence fertility preservation is of paramount importance. The mainstay of treatment is fertility sparing surgery (FSS) followed by active surveillance in selected cases or multidrug BEP (bleomycin, cisplatin, etoposide) chemotherapy. Evidence available on fertility following treatment of MOGCTs is scanty.The aim of this study is to evaluate the reproductive outcomes of patients treated with FSS for MOGCTs in MITO centres (Multicentre Italian trials in gynecologic oncology). Methodology: All the included patients were treated conservatively, both in primary surgery and for relapse. The indication on adjuvant chemotherapy in stage I disease varies among centres. Patients were sent a questionnaire evaluating their desire of conception, fertility and endocrine outcomes. Data were analyzed with descriptive statistics. Univariate and multivariate analyses were used to assess correlation between fertility outcomes and clinicopathological variables. Results: 164 patients were sent the questionnaire, that was completed by 114 patients (69.5%). Among all patients, 38 (33.3%) expressed a desire for pregnancy, 29 (76.3%) of which successfully conceived. 62.1% patients who conceived received adjuvant chemotherapy. 97, 7% conceptions occurred spontaneously. Six patients entered menopause after treatment (5.3%), 5 of whom received chemotherapy. No statistically significant difference was detected in terms of fertility outcomes between patients receiving adjuvant chemotherapy and those addressed to surveillance. When analysing factors affecting the pregnancy rate, the desire of conception was the only statistically significant factor. Conclusion: The results of the present study suggest that fertility outcomes in MOGCTs patients despite surgery and chemotherapy are very promising. The only factor significantly affecting the pregnancy rate after a MOGCTs diagnosis is the desire of conception.